2011
DOI: 10.1002/ajh.21941
|View full text |Cite
|
Sign up to set email alerts
|

Case–control study of risk factors of myelodysplastic syndromes according to World Health Organization classification in a Chinese population

Abstract: Risk factors of mydelodysplastic syndromes (MDS) remain largely unknown. We conducted a hospital-based case-control study consisting of 403 newly diagnosed MDS patients according to World Health Organization classification and 806 individually gender and age-matched patient controls from 27 major hospitals in Shanghai, China, to examine relation of lifestyle, environmental, and occupational factors to risk of MDS. The study showed that all MDS (all subtypes combined) risk factors included anti tuberculosis dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 42 publications
2
52
3
Order By: Relevance
“…Among northeastern patients, 50% were from rural zones and half of the cases were rural workers (data not shown). Farmers without protection devices, which are common in developing countries, are constantly exposed to these chemicals associated with MDS etiology [22]. A previous work that evaluated clinical characteristic of MDS from Ourense, Spain, where 70% of patients lived in rural environments, showed a frequency of 35% of RARS patients [38], consistent with the higher frequency of this subtype among Brazilian patients.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Among northeastern patients, 50% were from rural zones and half of the cases were rural workers (data not shown). Farmers without protection devices, which are common in developing countries, are constantly exposed to these chemicals associated with MDS etiology [22]. A previous work that evaluated clinical characteristic of MDS from Ourense, Spain, where 70% of patients lived in rural environments, showed a frequency of 35% of RARS patients [38], consistent with the higher frequency of this subtype among Brazilian patients.…”
Section: Discussionmentioning
confidence: 55%
“…The incidence and clinical characteristics of patients with MDS varies by geographical area, and this has been attributed to genetic or ethnic, occupational, lifestyle, and environmental factors, that have not been fully elucidated [9,22]. Socioeconomic status may also influence the outcome of the disease [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure to agricultural chemicals has been studied extensively as a risk factor, and most studies indicate a positive association with MDS [6,7,8,9,10,11,12], although in some others, no significant association was found [13,14]. A recent meta-analysis of 11 case-control studies confirmed a significant association between MDS and exposure to pesticides.…”
Section: Discussionmentioning
confidence: 77%